HRT in the perimenopause. An alternative for patients that do not wish to menstruate. Preliminary study - Siu, Alejandro (2015)
OBJETIVE: The present work aims at evaluating a way to administrate a drug named tibolone, among a group of patients having it as the unique therapy of hormonal replacement, but who still have some type of uterine bleeding and who are not still having definite menopause. The indication for the use of this drug is the presence of amenorrhea for at least one year. DESIGN: The idea is to administrate a combined hormonal treatment with pills derived from estrogens as well as progesterone in order to reduce to the minimal expression the endometrium, accompanied by an ultrasound assessment. RESULTS: It has been found that fifty percent of the studied patients responded satisfactorily to our therapeutic scheme. CONCLUSION: The fifty percent of the patients who have less than 7mm of endometrium, could use our therapy.